Empirical analysis of transaction malleability within blockchain-based e-Voting. Issue 100 (January 2021) - Khan, Kashif Mehboob; Arshad, Junaid; Khan, Muhammad Mubashir
Abstract: Blockchain is a disruptive technology that has been used to address a wide range of challenges in diverse domains including voting, logistics, healthcare and finance. Transaction malleability is one of the critical threats for blockchain, which can facilitate double-spending attacks by tampering with the state of a blockchain. This paper investigates the potential of transaction malleability attack within a blockchain-based application (e-voting) with the aim to identify settings which can lead to a successful transaction malleability attack. Therein, we aim to highlight conditions which can cause transaction malleability attack so as to help develop appropriate protection mechanisms. In particular, a successful execution of transaction malleability attack is presented which was conducted on a blockchain testbed hosting an e-voting application. The experiments identified significance of parameters such as network delay and block generation rate to successfully execute transaction malleability attack and have highlighted directions for future research.